Value of comparative genomic hybridization and fluorescence in situ hybridization for molecular diagnostics in multiple myeloma - Liebisch, Peter; Viardot, Andreas; Baßermann, Nicole; Wendl, Christiane; Roth, Katrin; Goldschmidt, Hartmut; Einsele, Hermann; Straka, Christian; Stilgenbauer, Stephan; Döhner, Hartmut; Bentz, Martin (British journal of haematology, 2003)
Summary. Chromosomal abnormalities, such as 13q deletions, are emerging as important prognostic factors in multiple myeloma. Fluorescence in situ hybridization (FISH) using specific DNA probes is the technique most widely used for the determination of genomic aberrations in this disease. The utility of comparative genomic hybridization (CGH) for molecular diagnostics in plasma cell malignancies has not been systematically analysed. We investigated tumour samples of patients with multiple myeloma (n = 43) or plasma cell leukaemia (n = 3) using CGH and FISH with five DNA probes localized to chromosome bands 1p22, 6q21, 11q22-q23, 13q14 and 17p13. By CGH, the most frequent genomic changes were gains on chromosomes 1q, 9q and 11q, as well as losses on chromosomes 13q, 6q, Xp and Xq. By FISH, trisomy 11q was identified at a similar frequency to the 13q deletion (42%). Compared with FISH data, the sensitivity of CGH was 80·7% and the specificity was 97·5%. Thirty-two aberrations found by FISH were not identified by CGH, mostly as a result of the proportion of cells carrying the respective aberrations, or because of the limited spatial resolution of CGH. Our data indicate that, for clinical molecular diagnostics in multiple myeloma, FISH with a disease-specific DNA probe set is superior to CGH analysis.